Lord of Arabia Ibn Saud : the intimate study of a king - Armstrong, H. C. (Harold Courtenay), 1891-1943. ); Darat al-Malik Abd al-Aziz (London: Kegan Paul, 2005)
Newly reissued, Lord of Arabia is the famous biography of Ibn Saud, King of Saudi Arabia, who continues to cst his shadow over the Middle East today. In this important study, the author reveals many of the family traditions and deeply-held principles that form the unwritten foundation of present-day Saudi Arabia and its neighbours. It ably recreates the King's life through key principal first-hand authorities, recording invaluable historical detail. -- Back cover
Published for the King Abdulaziz Foundation, Riyadh by Kegan Paul
1
Keywords: Abd al-Aziz, -- King of Saudi Arabia; Ibn Saud, -- King of Saudi Arabia, -- 1880-1953; Saudi Arabia -- Kings and rulers